Diversity in Schools: Immigrants and the Educational Performance of U.S. Born Students - David N. Figlio; Paola Giuliano; Riccardo Marchingiglio; Umut Özek; Paola Sapienza (Institute of Labor Economics (IZA), 2021)
We study the effect of exposure to immigrants on the educational outcomes of US-born students, using a unique dataset combining population-level birth and school records from Florida. This research question is complicated by substantial school selection of US-born students, especially among White and comparatively affluent students, in response to the presence of immigrant students in the school. We propose a new identification strategy to partial out the unobserved non-random selection into schools, and find that the presence of immigrant students has a positive effect on the academic achievement of US-born students, especially for students from disadvantaged backgrounds. Moreover, the presence of immigrants does not affect negatively the performance of affluent US-born students, who typically show a higher academic achievement compared to immigrant students. We provide suggestive evidence on potential channels.
Keywords: I21; I24; J15; 330; immigrant students; educational attainment